Sistematización de la segunda y tercera etapas de la primera cohorte. Facultad de Odontología, Universidad de Antioquia: 1996-1999 - Pineda-Suárez, Adrián Leandro; Beltrán-Salazar, Magda; Valencia-Ramírez, Consuelo; Posada-de Castaño, Patricia; Sierra-Lopera, Jorge Luis (Revista Facultad de Odontología Universidad de Antioquia, 2020)
The evaluation related to the proposal led to its systematization documenting and interpreting it through the experience of the second and third stages as a complement of the work done in the first stage. All of this was done taking into account the analysis of the organization, formation and participation of teachers, students, and administrative personnel of the School within a historical hermeneutic, ethnographic approach. Two workshops with both teachers and students that took part in the project, were held to gather and validate that experience using previous reconstructions of the research team based on documents, personal experience and reports of each of the seven semesters of the second and third stages. Descriptive analysis showed administrative failures in excessive hiring of teachers, in the evaluation and in the methodologies used. On the other hand, the analysis stood out the human and research development , both of them important aspects of the Curricular Transformation. Structural analysis led to define the curricular process developed in the different stages showing its threats and weaknesses and its strengths and possibilities of improvement. Inferential analysis concluded that many of the participants of the process were resistant to change, the analysis also showed improvisation and lack of coordination that led to the execution of things which were not planned; besides, the same analysis recognized the responsibility and the commitment of a few people that no matter the difficulties knew how to implement the proposal and the evaluation process.